Evaluasi Kesesuaian Lahan Tanaman Kelapa Dalam di Desa Jeruju Besar Kecamatan Sungai Kakap Kabupaten Kubu Raya - Wirantara, Fathan Madilla; Hazriani, Rini; Fadilla, Ulfia (Pedontropika: Jurnal Ilmu Tanah dan Sumber Daya Lahan, 2026)
Jeruju Besar Village in Sungai Kakap District, Kubu Raya Regency, has a coconut plantation managed by the community without considering the suitability of the land to the growing requirements of the plant, resulting in decreased coconut productivity. This study aims to identify land characteristics according to coconut criteria, determine land suitability subclasses, provide suggestions for improvements based on actual limiting factors. The study was conducted in Jeruju Besar Village, Sungai Kakap District, Kubu Raya Regency with an area of 50 ha for 6 months, including field surveys, soil sample analysis in the chemistry and soil fertility laboratory and physics and soil conservation. The grid method was used to determine 10 observation points (1 point represents 5 ha) by taking composite and intact soil samples at a depth of 0–30 cm. The map overlay results show two types of soil: Haplic Sulfaquents and Sulfic Endoaquepts. The actual land suitability of coconut is classified as unsuitable (N1) with the main limiting factors being rainfall, drainage, effective depth, CEC, and flood hazard. The potential is classified as marginally suitable (S2-r) with drainage limitations. Suggested improvements include water management through the construction of drainage channels to control excess water and remove toxins resulting from shallow sulfidic depths, the addition of organic materials to increase the CEC, and land management using the surjan system to overcome flooding.